Performance of Typha Angustifolia and Lepironia Articulata for Refurbishment Domestic Wastewater in an Integrated Phytogreen System - Nur Hamizah, H.; Abdul Syukor, Abd Razak; Suryati, Sulaiman (IJISET, 2015)
Treating wastewater is the way to overcome water shortage due to the water pollution problems. Wastewater is any water that has been adversely affected in quality by anthropogenic influence while clean water is produced from varies of wastewater treatment system. Therefore, this study is conducted to analyze the effectiveness of both bioremediation and phytoremediation in upgrading the wastewater treatment process by using two types of aquatic plants as phytoremediation agents; typha angustifolia and lepironia articulata. Phytogreen system reducing the main cost and maintenance cost of treating wastewater without ignoring the effectiveness of the system itself. Nevertheless, the aquatic plants itself is the important agents and the percentage interaction between absorption and adsorption to prove the effectiveness of this system.